Shenkang Injection for Treating Renal Fibrosis-Metabonomics and Regulation of E3 Ubiquitin Ligase Smurfs on TGF-β/Smads Signal Transduction - Zou, Junju; Zhou, Xiaotao; Chen, Xian; Ma, Yuerong; Yu, Rong (Frontiers in Pharmacology, 2022)
At present, TGF-β is the most critical fibrogenic factor known. Smad ubiquitin ligase Smurfs play an important role in the regulation of the TGF-/Smads signaling pathway, which is linked to metabolite changes in renal fibrosis. Previous studies have shown that Shenkang injection can prevent and treat chronic kidney disease through multiple channels of action. However, the precise relationship between Shenkang injection and the regulation of the TGF-/Smads signaling pathway in the treatment of chronic kidney disease is unknown. Here, we evaluated the pharmacological effects of Shenkang injection on ubiquitination and metabolic changes of the TGF-β/Smads signaling pathway in UUO mice using pathology-related indicators, immunoprecipitation, subcellular co-location, and metabonomics analysis. Our findings indicate that Shenkang injection can promote nuclear translocation of Smurf1 and Smurf2 to TGF- membrane receptors TR-I and Smad2 and ubiquitinated degradation of these proteins. Furthermore, the formation of TβR-I/TβR-II, TβR-I/Smad2, and TβR-I/Smad3 complexes was inhibited to negatively regulate the TGF-β/Smad signaling pathway induced renal tubular epithelial transdifferentiation (EMT). The EMT process is not very relevant in vivo, although it is clear that TGF-β induces EMT in cultured cells, which has been demonstrated by numerous teams around the world. However, this is not the case with the in vivo models of kidney fibrosis, especially UUO. In addition, Shenkang injection can improve amino acid metabolism, purine metabolism, and fatty acid metabolism disorders.